1999
DOI: 10.1002/(sici)1521-3927(19990601)20:6<299::aid-marc299>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The role of monomer in the chain transfer reaction in cobaloxime-mediated free-radical polymerization

Abstract: SUMMARY: The role of monomer in catalytic chain transfer polymerization was studied by determination of the chain transfer constants of the tetraphenyl derivative of cobaloxime boron fluoride (COPhBF) in methyl methacrylate at 60 8C varying the monomer concentration instead of the COPhBF concentration as is common practice. Toluene and tert-butyl acetate were used as diluents in these studies and it was found that the chain transfer constants obtained in the present studies were not significantly different fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Kukulj et al16 suggested that the continuously changing ratio of monomer to solvent may be a possible explanation for decreasing catalyst activity. However, Heuts et al18 tested this hypothesis by determining the chain transfer coefficients from experiments at constant catalyst concentrations and varying monomer concentrations and did not obtain any evidence in support of this hypothesis. Results on solvent effects, in which C T proved to be independent of toluene concentration, as discussed in a previous article29 point in the same direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kukulj et al16 suggested that the continuously changing ratio of monomer to solvent may be a possible explanation for decreasing catalyst activity. However, Heuts et al18 tested this hypothesis by determining the chain transfer coefficients from experiments at constant catalyst concentrations and varying monomer concentrations and did not obtain any evidence in support of this hypothesis. Results on solvent effects, in which C T proved to be independent of toluene concentration, as discussed in a previous article29 point in the same direction.…”
Section: Resultsmentioning
confidence: 99%
“…Some other studies were mainly focused on the production of dimer at high catalyst concentrations and subsequent copolymerization with other monomers 14, 15. Most kinetic studies were carried out in the group of Davis and Heuts 16–22. For nearly all studies molecular weight distributions did not or hardly change with conversion, whereas a decrease, which would be expected according to the Mayo equation (1), was only observed experimentally by Kowollik et al20 Several explanations have been suggested like catalyst deactivation and catalyst–solvent interactions that change with conversion and compensate for a decrease in monomer concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Gridnev [32] reported a similar effect of monomer purity on C T . Heuts et al [33] found that values in bulk and solution were almost the same only for Co(Ph) 4 BF, a tetraphenyl cobaloxime derivative. In that study both toluene and tertbutyl acetate were chosen as solvents, as no solvent complexation effects were expected.…”
Section: Effects Of Solvents and Solvent Impuritiesmentioning
confidence: 99%
“…(3)). This is clearly not observed and a plausible explanation for this result [19] other than (fortuitous) catalyst poisoning, [20,21] is not available at present. A summary of the final molecular weight parameters obtained from all the polymerizations is given in Tab.…”
Section: Molecular Weight Evolutionmentioning
confidence: 99%